HSP90 Contributes to chs3-2D-Mediated Autoimmunity - Lu, Junxing; Liang, Wanwan; Zhang, Nanbing; van Wersch, Solveig; Li, Xin (Frontiers in Plant Science, 2022)
Plants employ multi-layered immune systems to fight against infections by various pathogens. Different receptors are able to detect the invasion activities of pathogens, transduce signals to downstream components, and activate defense responses. Among those receptors, nucleotide-binding domain leucine-rich repeat containing proteins (NLRs) are the major intracellular immune receptor proteins. CHILLING SENSITIVE 3 (CHS3) is an Arabidopsis NLR with an additional Lin-11, Isl-1 and Mec-3 (LIM) domain at its C terminus. The gain-of-function mutant, chs3-2D, exhibiting severe dwarfism and constitutively activated defense responses, was selected as a genetic background in this study for a forward genetic screen. A mutant allele of hsp90.2 was isolated as a partial suppressor of chs3-2D, suggesting that HSP90 is required for CHS3-mediated defense signaling. In addition, HSP90 is also either fully or partially required for the autoimmunity of the Dominant Negative (DN)-SNIPER1 and gain-of-function ADR1-L2 D484V transgenic lines, suggesting a broad role for HSP90 in NLR-mediated defense. Overall, our work indicates a larger contribution of HSP90 not only at the sensor, but also the helper NLR levels.